Predictors of the risk of developing diabetic retinopathy in type 2 diabetes mellitus and primary open-angle glaucoma in the course of a comorbid condition - K. A. Gudzenko; S.Iu. Mogilevskyy (Ukrainian Society of Ophthalmologists, 2021)
Background: Diabetic retinopathy DR in type 2 diabetes mellitus (T2DM) and primary open-angle glaucoma (POAG) share some common pathogenetic mechanisms, raising the possibility that, in the course of a comorbid condition, the two diseases may exacerbate each other. Purpose: To use regression analysis in order to determine the predictors of the development of DR in T2DM and POAG in the course of a comorbid condition. Material and Methods: We examined 649 patients (649 eyes). These included 301 (301 eyes) with both DR and POAG; 164 (164 eyes) with DR but no POAG; 81 (81 eyes) with POAG but no T2DM; and 103 (103 eyes) having neither T2DM nor POAG (controls). Severity of DR was graded as per the 2002 guidelines of the American Academy of Ophthalmology. The stage of POAG was determined according to the classification of perimetric changes. Multivariate logistic regression analysis was used to develop models in Statistica 10 (GLZ; StatSoft, Tulsa, OK). Results: Blood glucose above 6.05 mmol/l, glycated hemoglobin above 6.1% and female gender were found to be independent predictors of the risk of developing DR. Patient age and the presence, stage and duration of POAG had no impact on the risk of developing DR. Duration of T2DM, elevated IOP and female gender were found to be positive predictors, whereas best-corrected visual acuity (BCVA), a negative predictor of the risk of developing POAG. Patient age, carbohydrate metabolic compensation indices and the stage of DR had no impact on the risk of developing POAG. A regression model was developed, allowing to predict the development of POAG with a total prediction accuracy of 85.7% (OR, 35.82; 95% CI, 22.92-56.00). The cut-off values of the predictors of developing POAG were a duration of T2DM above 3.5 years (accuracy, 60.2%), IOP above 23.2 mmHg (accuracy, 85.1%), and BCVA below 0.8 (accuracy, 70.3%). Conclusion: Blood glucose above 6.05 mmol/l, glycated hemoglobin above 6.1% and female gender were independent predictors of the risk of developing DR. Duration of T2DM and elevated IOP were predictors of the risk of developing POAG.